Cost of Hepatitis C care facilitation for HIV/Hepatitis C Co-infected people who use drugs. (1st March 2022) - Gutkind, Sarah; Starbird, Laura E.; Murphy, Sean M.; Teixeira, Paul A.; Gooden, Lauren K.; Matheson, Tim; Feaster, Daniel J.; Jain, Mamta K.; Masson, Carmen L.; Perlman, David C.; Del Rio, Carlos; Metsch, Lisa R.; et al.
Abstract: Background: Using data from a randomized trial, we evaluated the cost of HCV care facilitation that supports moving along the continuum of care for HIV/HCV co-infected individuals with substance use disorder. Methods: Participants were HIV patients residing in the community, initially recruited from eight US hospital sites. They received HCV care facilitation (n = 51) or treatment as usual (n = 62) for up to six months. We used micro-costing methods to evaluate costs from the healthcare sector and patient perspectives in 2017 USD. We conducted sensitivity analyses varying care facilitator caseloads and examined offsetting savings using participant self-reported healthcare utilization. Results: The average site start-up cost was 6320 (site range: 4320-7000), primarily consisting of training. The mean weekly cost per participant was 20 (site range: 4-30) for care facilitation visits and contacts, 360 (site range: 130- 700) for supervision and client outreach, and 70 (site range: 20-180) for overhead. In sensitivity analyses applying a weekly caseload of 10 participants per care facilitator (versus 1–6 observed in the trial), the total mean weekly care facilitation cost from the healthcare sector perspective decreased to 110. Weekly participant time and travel costs averaged 7. There were no significant differences in other healthcare service costs between participants in the intervention and control arms. Conclusion: Weekly HCV care facilitation costs were approximately 450 per participant, but approximately 110 at a real-world setting maximum caseload of 10 participants per week. No healthcare cost offsets were identified during the trial period, although future savings might result from successful HCV treatment. Highlights: Care facilitation weekly cost was 450 per HIV/HCV co-infected trial participant. The weekly cost was lower (110 per person) assuming a more realistic caseload. Outreach and supervision represented the largest share of care facilitation costs. No healthcare cost offsets were identified during the trial period.